The Insurance Premium in the Interest Rates of Interlinked Loans in a Small-scale Fishery - Marie-Catherine Riekhof (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
Interest payments based on income flows are a common feature of informal loans. Such so-called `interlinked loans' can be seen as an insurance against very low disposable incomes, as interest payments are lowest when income turns out to be low. This paper examines whether interlinked loans indeed contain an insurance premium and how those premia are determined. A simple theoretical model predicts that interest rates of interlinked loans increase with income volatility when insurance premia exist. Based on data from a small-scale fishery in India, calculations show that on average, lenders receive 25% of the income, which corresponds to an average interest rate of 49% p.a.. A panel data analysis confirms theoretical predictions that interlinked loans contain an insurance component paid by the borrowers.
Keywords: O16; O17; Q22; H23; Q54; O31; 330; Interlinked loan; Insurance premium; Interest rate; Small-scale fishery; Informal insurance; Informal credit markets; Interlinked contracts; Risk-sharing; India; Kreditgeschäft; Zins; Kreditrisiko; Kleinfischerei; Indien